Licensing and relegation : a totalitarian trade regime and dealers' tactics - Flick, Caroline (Journal for art market studies, 2019)
Among the archival records pertaining to the Berlin Head Office of the National Socialist Reich’s Chamber of Fine Arts a list of forty-four art dealers’ names for registration with the new Chamber can be found. The focus of this article is on events surrounding this archival record, dealing exclusively with the trade section within the Reich’s Chamber of Fine Art and focusing on individuals rather than firms. The Reich’s Chamber of Culture was established in order to standardise “cultural creation”, with its jurisdiction ultimately empowered to cover activities of art production, reception and distribution. As the Weimar Republic was transformed into a totalitarian state, the Reich’s Chamber of Culture was created by evoking the nomenclature of Chambers of Commerce and trading regulations but intending direct control of individuals as well as activities. As a consequence, its influence was felt throughout the entire art market and initiated a market disturbance which reverberates to the present time, necessitating ongoing market research and price analysis. The dealers whose professional activities were controlled by the new licensing regulation developed different strategies to mitigate its effects, ultimately demonstrating a limited measure of agency under a totalitarian regime.